Pseudococyclic Partial Hadamard Matrices over Latin Rectangles - Raúl M. Falcón; Víctor Álvarez; María Dolores Frau; Félix Gudiel; María Belén Güemes (Mathematics, 2021)
The classical design of cocyclic Hadamard matrices has recently been generalized by means of both the notions of the cocycle of Hadamard matrices over Latin rectangles and the pseudococycle of Hadamard matrices over quasigroups. This paper delves into this topic by introducing the concept of the pseudococycle of a partial Hadamard matrix over a Latin rectangle, whose fundamentals are comprehensively studied and illustrated.